An improved implementation of construction waste management initiatives in Malaysia / Nurzalikha Sa’adi - Sa’adi, Nurzalikha (2016)
Illegal dumping of construction waste is indeed a key issue to be addressed in achieving environmental sustainability. A higher demand for new developments in Malaysia has led to the increase in construction activities, which result in a significant impact on the environment. Thus, it is important for the Malaysian government to address this issue. With that, this research had developed strategies that can be implemented pertaining to construction waste management initiatives in Malaysia. In order to achieve the stated aim, the objectives outlined in this research had been cascaded to identify the issues that reflected the existing construction waste management initiatives in Malaysia; to explore the implementation of initiatives in managing construction waste; and to propose recommendations to further improve the implementation of construction waste management initiatives in Malaysia. Hence, mixed methods of both qualitative and quantitative approaches had been adopted. The result also supported by a validation survey through a likert scale survey. The obtained results indicated that the construction waste management initiatives offered by the government were insufficient in terms of inert landfill to meet the increasing construction waste generated and seemed to be less efficient due to lack of enforcement, as well as implementation. Even though the Malaysian government attempts to assist stakeholders in managing construction wastes and moving towards sustainable construction practices through the initiatives, it seems to be less efficient because there are lack of enforcement and implementation. Hence, the government required to enforce the initiatives by providing a legislative and regulations to manage construction waste. The role among the Malaysian government authorities in managing construction waste also needs to restructure and improve by embedding the duties to local authorities. In short, the monitoring and inspection by government authorities are very important to ensure the contractor implement the construction waste management on site effectively. Apart from that, awareness on the existing construction waste management initiatives is crucial in ensuring the effectiveness of the construction waste management initiatives implemented in Malaysia. Thus, the government and contractors play a significant role to implement the construction waste management initiatives effectively to achieve the sustainable development. A set of recommendations pertaining to the implementation of construction waste management initiatives in Malaysia had been proposed in ensuring the achievement of sustainable development, besides indirectly improving the quality of construction waste management in Malaysia.